Outcome and Accountability in Cross-sector Collaboration in the Implementation of Integrated Slum Area Alleviation with Relocation Pattern in South Bolaang Mongondow Regency - Ohy, Marzanzius Arvan (KnE Social Sciences, 2025)
Slum problems often occur because of the gap between the need for housing and the low economic status of the community. Slums not only have an impact on the aesthetics of the city, but also have a broad impact on society in terms of health, crime, and economic problems. This research aims to analyze outcomes and accountability in cross-sector collaboration in the implementation of integrated slum alleviation with a relocation pattern in South Bolaang Mongondow Regency. It uses a qualitative approach, and collects data through observation, in-depth interviews, and documentation. Data sources consist of primary and secondary data, while data analysis is conducted using interactive methods. The informants in this research are stakeholders directly involved in the implementation of the Integrated Slum Upgrading Policy with Relocation Pattern. The findings indicate that outcome and accountability aspects still face potential conflicts, particularly among the relocated communities. These include social disruptions, difficulties adapting to new environments, and adverse economic impacts. Although challenges remain, the policy’s accountability has been formally implemented through legal, social, and economic frameworks, ensuring that each sector fulfills its respective responsibilities in a structured manner.